Complete Genome Sequences of Six Measles Virus Strains - Phan, My V. T.; Schapendonk, Claudia M. E.; Oude Munnink, Bas B.; Koopmans, Marion P. G.; de Swart, Rik L.; Cotten, Matthew (Genome announcements (Washington, DC), 2018)
Genetic characterization of wild-type measles virus (MV) strains is a critical component of measles surveillance and molecular epidemiology. We have obtained complete genome sequences of six MV strains belonging to different genotypes, using random-primed next generation sequencing.